Ranking of Innovation Factors of Employees' Job Performance - Darwish Abdulla Lari, Mohamed Ahmed; Abdul Hamid, Norhadilah; Darwish Lari, Fatima Ahmed (International Journal of Sustainable Construction Engineering and Technology, 2020)
This paper presents the ranking of innovation factors affecting employees' job performance of Abu Dhabi government sector. Three hundred questionnaires were distributed among employees in the Ministry of Culture, Youth and Community Development UAE.  The respondents were requested to rate 23 identified innovation factors which are clustered into four groups using 5-point Likert scale with scale 5 for extremely significant to scale 1 for not significant. However only 265 valid responses were recovered from the survey. The data collected from the survey was analyzed descriptively using mean score index and standard deviation to determine the ranking of each factor. For product innovation group, the highest rank of factor is product extension through technologically new products; while in marketing innovation the highest rank of factor is improving sales promotion tools; subsequently, in process innovation the highest ranked of factor is develop new and improve production layout and lastly, in organization innovation the highest ranked of factor is effective and efficient work processes. The findings from this study hopefully can benefit the government organization performance.